The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2024
DOI: 10.3389/fendo.2023.1310000
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, distribution, and effects of growth regulation of MC3R and MC4R in red crucian carp (Carassius auratus red var.)

Lu Huang,
Xin Deng,
Xiangqiong Yang
et al.

Abstract: BackgroundMelanocortin-3 and -4 receptors (MC3R and MC4R), G protein-coupled receptors, play vital roles in the regulation of energy homeostasis. To understand the functions of mc3r and mc4r in the energy homeostasis of red crucian carp (Carassius auratus red var., RCC), we cloned mc3r and mc4r, analyzed the tissue expression and localization of the genes, and investigated the effects of knockout of mc3r (mc3r+/-) and mc4r (mc4r+/-) in RCC. ResultsThe full-length cDNAs of RCC mc3r and mc4r were 1459 base pairs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 91 publications
0
1
0
Order By: Relevance
“…Carassius auratus red var. accounts for an important proportion of freshwater aquaculture production worldwide, but it is susceptible to various factors during production [29]. A previous study by our research group showed that NP affects C. auratus red var.…”
Section: Introductionmentioning
confidence: 90%
“…Carassius auratus red var. accounts for an important proportion of freshwater aquaculture production worldwide, but it is susceptible to various factors during production [29]. A previous study by our research group showed that NP affects C. auratus red var.…”
Section: Introductionmentioning
confidence: 90%